2013
DOI: 10.1080/13540602.2013.744201
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated instruction in teacher education: A case study of congruent teaching

Abstract: Teachers are supposed to use forms of differentiated instruction to anticipate the differences among their students. However, the adaptation of teaching to the diversity of the group often takes place with difficulty. Teacher education is blamed for not preparing student teachers adequately for differentiated instruction. Several authors suggest that congruent teaching in teacher education might be an adequate solution to this problem.This case study aims to investigate the (congruent) realization of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 30 publications
1
26
0
11
Order By: Relevance
“…Kategorien begrunnes med at det å eksplisitt modellere arbeidsformer og metoder ikke er nok, studentene må også bli oppmuntret til å reflektere over 5 meningen med modelleringen (Loughran & Berry, 2005, s. 193, 200;Ruys et al, 2013). Et forslag til en måte å koble teori og praksis er å eksplisitt modellere underliggende pedagogiske valg og videre vise hvordan valgene kan analyseres ved hjelp av teori.…”
Section: Abstract: Teacher Education; Explicit Modelling; Teaching; Dunclassified
See 1 more Smart Citation
“…Kategorien begrunnes med at det å eksplisitt modellere arbeidsformer og metoder ikke er nok, studentene må også bli oppmuntret til å reflektere over 5 meningen med modelleringen (Loughran & Berry, 2005, s. 193, 200;Ruys et al, 2013). Et forslag til en måte å koble teori og praksis er å eksplisitt modellere underliggende pedagogiske valg og videre vise hvordan valgene kan analyseres ved hjelp av teori.…”
Section: Abstract: Teacher Education; Explicit Modelling; Teaching; Dunclassified
“…Et forslag til en måte å koble teori og praksis er å eksplisitt modellere underliggende pedagogiske valg og videre vise hvordan valgene kan analyseres ved hjelp av teori. Dette gjøres ved at laereren modellerer hvordan metakommentarer kan knyttes til praktiske eksempler (Ruys et al, 2013;Ulvik & Smith, 2016, s. 63). I denne sammenhengen poengterer Lunenberg at: «This means that the next step in modelling is to move on from making useful 'tricks' explicit to student teachers to connecting exemplary behaviour with theory» (Lunenberg et al, 2007, s. 592).…”
Section: Abstract: Teacher Education; Explicit Modelling; Teaching; Dunclassified
“…Giving meta-commentary is a crucial aspect of the pedagogical behavior of teacher educators. Provision of meta-commentary is not evident among teacher educators (Bullough, 1997;Ruys et al, 2013). The researchers concluded that the observed teacher educator was not considered as a role model on the subject of differentiated instruction in the view of student teachers.…”
Section: Congruent Teaching In Teacher Educationmentioning
confidence: 99%
“…9;2014 the workshop, the teacher educators' ability to link their own teaching to theory had improved. Therefore, Swennen et al (2008) Only a limited number of studies focus on the congruent teaching and meta-commentary among teacher educators (Ruys et al, 2013;Swennen et al, 2008). This study investigates a language teacher educator's congruent teaching of a task-based approach in a TESOL course in a language teacher education program in Taiwan.…”
Section: Congruent Teaching In Teacher Educationmentioning
confidence: 99%
See 1 more Smart Citation